Impact of high triglyceride/high-density lipoprotein cholesterol ratio (insulin resistance) in ST-segment elevation myocardial infarction. Issue 43 (23rd October 2020) - Chen, Huang-Chung; Lee, Wei-Chieh; Fang, Hsiu-Yu; Fang, Chih-Yuan; Chen, Chien-Jen; Yang, Cheng-Hsu; Wu, Chiung-Jen
Abstract : Abstract: The ratio of triglyceride (TG)/high-density lipoprotein cholesterol (HDL-C) has been proposed as an easily obtainable atherogenic marker and high TG/HDL-C ratio is associated with insulin resistance. This study investigated the associated between a high TG/HDL-C ratio and cardiovascular mortality in patients with ST-segment elevation myocardial infarction (STEMI), with or without diabetes mellitus (DM). Between January 2005 and December 2014, 1661 patients with STEMI underwent primary percutaneous coronary intervention in our hospital. Of these, 289 were classified into group 1 (with both DM and a high TG/HDL-C ratio), 295 into group 2 (with DM, but without a high TG/HDL-C ratio), 501 into group 3 (without DM, but a high TG/HDL-C ratio), and 576 into group 4 (without DM or a high TG/HDL-C ratio). Older age, longer chest pain to reperfusion time, poor hemodynamic condition, and higher prevalence of multiple vessel coronary artery disease were noted in those with DM. Poor outcomes including higher 30-day and 1-year cardiovascular mortality and all-cause mortality rates were noted in those with DM but without a high TG/HDL-C ratio. Patients with DM but without a high TG/HDL-C ratio had a Hazard ratio of 3.637 for cardiovascular mortality relative to those without DM, but without a high TG/HDL-C ratio. Even though a high TG/HDL-C ratio is associated with insulin resistance, patients with or without DM, but with a high TG/HDL-C ratio had better 30-day and 1-year outcomes.